PERANCANGAN SOLAR CELL SEBAGAI SUMBER ENERGI LISTRIK ALTERNATIF UNTUK PENERANGAN LOBBY FAKULTAS TEKNIK UNIVERSITAS RIAU KEPULAUAN - Roma Gustiawan; Endang Susanti; Pamor Gunoto (SIGMA TEKNIKA, 2019)
Electricity is one of the most important needs of the community electricity shorttages are very disturbing human activities as well as the University of Riau Islands campus is very dependent on electricity supply from PLN, because this campus conducts tearning activities at night, the current energy is mustly fulfilled by fosil fuel energy such as petroleum, coal and natural gas but the supply of this energie is decreasing, PLN which as a supply of electricity is very dependent on fossil fuels so that PLN can at any time turn out blackouts on the campus of the University of Riau Islands very disturbed with the rilling blackout because the campus will be dark.there needs to be alternative energy at least illuminating as long as the electricity from PLN is on, this research and design is to build asolar electricity supply sistem to help temporary lighting in this design. PLTS is utilized as Alternative electrical energy to illuminatethe lobby of the Faculty of engineering Universitas Riau.Byusing50Wp solar cell panel,charge controller to maintain the stability of the sistem and 42 Ah batrtery, by using this sistem Dc lamps as a load of 54 Watt batrei capacitycan be lit during a blackout from the PLN.